2013
DOI: 10.1631/jzus.b1300001
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine biodegradation efficiency, metabolite detection, and trzD gene expression by enrichment bacterial cultures from agricultural soil

Abstract: Abstract:Atrazine is a selective herbicide used in agricultural fields to control the emergence of broadleaf and grassy weeds. The persistence of this herbicide is influenced by the metabolic action of habituated native microorganisms. This study provides information on the occurrence of atrazine mineralizing bacterial strains with faster metabolizing ability. The enrichment cultures were tested for the biodegradation of atrazine by high-performance liquid chromatography (HPLC) and mass spectrometry. Nine cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 48 publications
2
22
0
1
Order By: Relevance
“…As expected, in the long‐term assay, an overall decrease in atrazine phytotoxicity occurred relative to the short‐term analysis. This result is consistent with the drastic reduction in atrazine levels in the soil over time in all treatments, which may have occurred due to herbicide degradation by microbial and physicochemical processes …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, in the long‐term assay, an overall decrease in atrazine phytotoxicity occurred relative to the short‐term analysis. This result is consistent with the drastic reduction in atrazine levels in the soil over time in all treatments, which may have occurred due to herbicide degradation by microbial and physicochemical processes …”
Section: Discussionsupporting
confidence: 87%
“…This result is consistent with the drastic reduction in atrazine levels in the soil over time in all treatments, which may have occurred due to herbicide degradation by microbial and physicochemical processes. [46][47][48] Moreover, the comparison between cotyledonary and trifoliate leaves on the residual effects of all atrazine-containing formulations on macroscopic symptoms and physiological parameters indicated a gradual recovery of soybean plants from atrazine phytotoxicity. More importantly, we observed that tenfold-diluted nanoatrazine had a lower inhibitory effect on the photosystem II activity of trifoliate leaves and root dry matter accumulation than nano-and non-nanoatrazine at standard dosage, as well as it resulted in lower atrazine levels in the soil.…”
Section: Discussionmentioning
confidence: 96%
“…Complete mineralization is the most favorable way of biodegradation; however, the vast majority of the xenobiotics biodegradation pathways (including triazines) end in the formation of by-products. Formation of ametryn metabolites during the experiments presented in this work is partially in agreement with the reactions of atrazine biodegradation, where the formation 2-hydroxyatrazine has been observed in many species (Atrazine Pathway Map, 2017; KEGG Atrazine degradation -Reference pathway, 2017; Govantes et al, 2009;Solomon et al, 2013;Abigail et al, 2013), while deethylation of ethanamine substituents seems to be characteristic for fungal strains and mammals (Chirnside et al, 2011;Pereira et al, 2013, Sciali et al, 2014. Figure 6.…”
Section: Discussionsupporting
confidence: 85%
“…The 16S rRNA gene was amplified by PCR as described by Solomon et al [13] using 16S rRNA gene specific 27F and 1492 universal primers. The amplified product was purified by QIAquick PCR purification kit (Qiagen, USA) according to the manufacturer's instruction, cloned into pGEM-T easy vector (Promega, USA) and confirmed positive clone was sequenced by Applied Biosystems 3730XL DNA analyzer with the sequencing reaction components derived from BigDye Terminator v3.1 cycle sequencing kit (Applied Biosystems, USA).…”
Section: Methodsmentioning
confidence: 99%